2016
DOI: 10.1016/j.ejmp.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The 68 Ge phantom-based FDG-PET site qualification program for clinical trials adopted by FIL (Italian Foundation on Lymphoma)

Abstract: The (68)Ge phantom proved a reliable tool for PET scanner qualification, able to significantly reduce the potential sources of error while increasing the reproducibility of PET derived quantitative parameter measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…However, to our knowledge, no ongoing trials have been launched using the TMTV to guide therapy. Even if the prerequisite for this type of trial is quality control, as done using various existing control systems (7,19,20), it is anyway required for good PET clinical practice. The main problem is which TMTV technique measurement should be chosen because there is no established consensus.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, no ongoing trials have been launched using the TMTV to guide therapy. Even if the prerequisite for this type of trial is quality control, as done using various existing control systems (7,19,20), it is anyway required for good PET clinical practice. The main problem is which TMTV technique measurement should be chosen because there is no established consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that variability across a network of hospitals can vary based on whether long-lived 68 Ge/ 68 Ga or short-lived 18 F sources are used (35). We note that there is a subtlety in quality control of SUVs, in that short-lived phantoms can detect more sources of variability but cannot separate them.…”
Section: Discussionmentioning
confidence: 99%
“…Long-lived phantoms can separate bias instability in the scanner and dose calibrator and follow extremely stable decay curves, but may miss effects such as clock synchronization or incomplete dose injection. Short-lived phantoms are commonly used to assess scanner bias for clinic accreditation (3537), and in 1 such study, 12% of scanners tested (N = 101) were found to have biases >10% (36). This shows that quality control for PET is essential, and we believe that long-lived sources have a key role to play in characterizing SUV variability in time.…”
Section: Discussionmentioning
confidence: 99%
“…Effort of cross-calibration through the measurements of different phantoms permits achievement of a variability less than 10% in multi-centre clinical trials [23,24,25,26,27,28,29,30], while 5% should be a good requirement for using PET/CT in a quantitative way [31,32]. …”
Section: Sources Of Errors In Uptake Evaluationmentioning
confidence: 99%
“…The response was assessed by adopting the 5-point scale Deauville criteria as a qualitative index and the SUV max as a quantitative index. A response was defined as a reduction in the Deauville score or, if there was no change in it, a reduction in SUV compared to baseline.Scanners underwent clinical trial qualification for semi-quantitative analysis from the FIL core lab [30]. That is, before patients’ accrual, all PET/CT sites acquire two phantoms and sends them to the core lab.…”
Section: Strategies Of Error Reduction In Onco-heamatological Clinmentioning
confidence: 99%